1999
DOI: 10.1017/s0021859698006078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of headbugs (Eurystylus sp.) on sorghum grain mould in the Nigerian savanna

Abstract: The interaction between headbugs (Eurystylus sp.) and grain mould (GM) on sorghum was examined in field trials carried out at Samaru, Nigeria in the 1995 and 1996 wet seasons. The results obtained show that in all three sorghum cultivars tested, insect damage increased the number of fungal colonies associated with the grain. This resulted in lower germination, 1000-grain mass and yield in such treatments. Insect damage also altered the relative abundance of the common fungal flora species as, following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Experiments carried out by IER at Sotuba, Mali, in 1990 and clearly demonstrated the strong relationship between head-bugs and grain molds. This was confirmed in experiments conducted by IAR at Samaru, Nigeria, in 1995(Marley and Malgwi, 1999.…”
Section: Introductionsupporting
confidence: 68%
“…Experiments carried out by IER at Sotuba, Mali, in 1990 and clearly demonstrated the strong relationship between head-bugs and grain molds. This was confirmed in experiments conducted by IAR at Samaru, Nigeria, in 1995(Marley and Malgwi, 1999.…”
Section: Introductionsupporting
confidence: 68%
“…The degree of mouldiness (discoloration) of threshed grains was examined on 30 g of seeds spread over a glass dish using a stereomicroscope (magnification 30×) (Audilakshmi et al ., 1999). Discoloration was assessed as a percentage of the discoloured grain surface per total area of the grain (Marley & Malgwi, 1999). The 1000‐grain weight was determined on a sensitive balance (Type B6100, Sartorius GMBH).…”
Section: Methodsmentioning
confidence: 99%
“…A similar increment in the incidence of grain mould pathogens and consequent reduction in sorghum grain weight and germination due to infestation by sorghum head bug (E. oldO were reported (Marley & Malgwi, 1999). Infestation of sorghum panicles by E. immaculatus was shown to increase the incidence of grain mould and grain hardness, germination and weight (Sharma et al, 1992).…”
Section: Discussionmentioning
confidence: 52%
“…Studies on weather variables and host related factorh that affect sorghum grain mould have shown that tempe;ature, relative humidity and grain development stage significantly influence the severity of grain mould (Bandyopadhyay et al, 1991;Singh & Agarwal, 1993;Tarekegn, McLaren & Swart, 2004). Other studies on the relationship between biotic factors and sorghum grain mould development emphasised the role of panicle insects (Sharma et aI., 1992;Sharma et aI., 1994;Marley & Malgwi, 1999;Sharma et al, 2000) colonising panicles. Marley and Malgwi (1999) demonstrated that grain mould fungi (F thapsinum, P sorghina and C. lunata) increased while grain yield and germination decreased in sorghum infested by head bugs (Eurystylus oldi Poppius) compared with uninfested ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation